Development and Implementation of an Advanced Analytical Approach for Flexible Pavement Analysis and Design in Western Australia - Khobklang, Pakdee (Curtin University, 2015)
An advanced method for analysis of pavement having thin wearing surface layer is proposed. A mechanistic approach, based on disturbed state concept, was adopted for material modelling. A 3D column-strip model of pavement structures was then introduced using finite element method. Results indicate that the proposed approach can be used in predicting the permanent deformation of pavement structures and provides realistic resultant stresses and deformations because important engineering properties can be incorporated in the calculation.